Peran Satuan Brigade Mobil dalam Penanganan Demonstrasi Massa (Studi Kasus: Wilayah Kabupaten Kotawaringin Timur): The Role of the Mobile Brigade Unit in Handling Mass Demonstrations (Case Study: East Kotawaringin Regency) - Tiono, Muhamad Ilham; Saipul, Saipul; Fatchurahman, M. (Anterior Jurnal, 2025)
Mass demonstrations are a form of expressing aspirations that are protected by the constitution in Indonesia. However, these actions often have the potential to disrupt public order, especially if they turn into riots or anarchic actions. The Mobile Brigade Unit (Brimob) of the Indonesian National Police has a strategic role in handling these situations to maintain the stability of security and public order. This study aims to analyze the role of Brimob in handling mass demonstrations, the strategies implemented, and the challenges faced. The research method used is a qualitative method with a descriptive-analytical approach, involving data collection through interviews, observations, and document studies. The results of the study indicate that Brimob plays an important role in controlling the masses, securing vital objects, and taking action against situations that have the potential to be anarchic. The strategies implemented include a preventive approach through intelligence, layered security, and proportional use of force. However, in its implementation, Brimob faces challenges such as mass dynamics, public pressure, limited resources, and coordination between agencies. This study recommends increasing Brimob's training capacity, strengthening operational equipment, and developing a humanistic and collaborative approach to support success in handling mass demonstrations. With these steps, it is hoped that Brimob can carry out its role more effectively, professionally, and in a balanced manner in maintaining security and order amidst the dynamics of society.